2013
DOI: 10.1109/led.2013.2278214
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Plasma Functionalized Multiwalled Carbon Nanotube Thin Film as A pH Sensing Membrane of Extended-Gate Field-Effect Transistor

Abstract: Abstract-High-performance pH sening membranes of extended-gate field-effect transistors (EGFETs) composed only of oxygen-plasma-functionalized carbon nanotube thin films (CNTFs) are demonstrated. A large number of oxygen-containing functional groups are decorated on the sidewalls of carbon nanotubes (CNTs) after the oxygen plasma treatment. These functional groups act as the sensing sites and accurately respond to the ions of interest in different pH levels. Therefore, these functionalized CNTFs as the pH-EGFE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Compared to the pristine CNTs (P-CNTs), the rough surface of O-CNTs indicated that the outer-surface of P-CNTs was mildly etched by oxygen active species during O 2 plasma treatment, creating defects on the surface of O-CNTs. It is noteworthy that the plasma reactor used in this work has a maximum RF power of only 18 W, which is much weaker than the power used in conventional CNT O 2 -plasma modification, leading to a mild surface functionalization without dramatic structural damage. The carbon nanotube was paved into an ultrathin layer to homogeneously expose it to O 2 plasma (Figure S1).…”
mentioning
confidence: 99%
“…Compared to the pristine CNTs (P-CNTs), the rough surface of O-CNTs indicated that the outer-surface of P-CNTs was mildly etched by oxygen active species during O 2 plasma treatment, creating defects on the surface of O-CNTs. It is noteworthy that the plasma reactor used in this work has a maximum RF power of only 18 W, which is much weaker than the power used in conventional CNT O 2 -plasma modification, leading to a mild surface functionalization without dramatic structural damage. The carbon nanotube was paved into an ultrathin layer to homogeneously expose it to O 2 plasma (Figure S1).…”
mentioning
confidence: 99%
“…In the absence of CO 2 , there is no peak correlated with oxygen-containing species. On the other hand, as CO 2 is introduced into the PECVD reactor, XPS C 1s spectra split into several peaks, including C–O, CC, and C–OC peaks; such oxygen-containing species, including R–OH and R–OOH, result from the reactions of O atoms with unsaturated carbon. …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, EGFET reveals many advantages over the conventional ISFET with low cost, simple to package with the FET isolated from its chemical environment, flexible shape of the extended-gate structure, and good long-term stability. [10][11][12] Recently, pH SEs using nanostructured materials such as zinc oxide (ZnO) based materials, 10,13,14) titanium oxide (TiO 2 ), [15][16][17] tin oxide (SnO 2 ), 18) vanadium pentoxide (V 2 O 5 ), 19,20) tungsten oxide (WO 3 ), 21,22) multi-walled carbon nanotube (MWCNT), [23][24][25][26][27] nickel oxide (NiO), 28,29) etc., to enhance the sensitivity of pH sensors was demonstrated. It shows that the increase in the amount of ion adsorption sites through increasing the surface area (SA) of metal oxides and MWCNT nanostructures, in addition to the material itself, is very beneficial for ion sensing.…”
Section: Introductionmentioning
confidence: 99%